Abrasion-resistant lining plate material for semi-autogenous mill and preparation method of abrasion-resistant lining plate material
By using specific weight components and process processing in the semi-self-grinder lining material, abrasive lining with high strength, toughness and corrosion resistance is formed, which solves the problem of existing materials being easily deformed and worn in large semi-self-grinders, and achieves a longer service life and lower operating costs.
Patent Information
- Application Number
- CN202510113367.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-04
AI Technical Summary
The existing semi-self-grinding lining materials are prone to plastic deformation, serious wear loss and short service life in large semi-self-grinding machines, resulting in increased operating costs.
A wear-resistant lining material including specific weight components is used to form a material with reasonable strength, tough matching and corrosion resistance through medium frequency induction furnace steelmaking, water glass sand casting, annealing and stress-relieving tempering treatment.
It realizes abrasion-resistant lining plate for long-term use in large impact loads and slurries with certain corrosive media, improves the strength, toughness and corrosion resistance of the material and extends the service life.
Smart Images

Figure CN119553177A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lining materials, and in particular to a wear-resistant lining material for a semi-autogenous mill and a preparation method thereof. Background Art
[0002] In addition to the steel balls, the easily worn parts in the SAG mill are all kinds of linings. The linings protect the mill cylinder in the SAG mill from ore impact, wear, corrosion and increase the strength of the cylinder. As the size of the SAG mill increases, the weight of the linings also increases accordingly. In a SAG mill with a size of 10.37×5.19m, the total weight of the whole set of linings reaches 440t, the maximum weight of a single cylinder lining reaches 2t, and the maximum length exceeds 2m. At the same time, as the size of the SAG mill increases, the size of the steel balls used as grinding bodies in the SAG mill also increases. The diameter of the steel balls is usually greater than 100mm, and the maximum diameter can reach 200mm. As the size of the SAG mill and the steel balls increases, the energy of the steel balls falling and impacting the ore and the lining increases. Table 1 shows the impact energy of steel balls of different sizes in SAG mills of different sizes.
[0003] Table 1 SAG mill, steel ball diameter and impact energy of a single steel ball ;
[0004] Therefore, the SAG mill lining, especially the cylinder lining, must have good impact resistance, high hardness and corrosion resistance to resist the impact of steel balls and ore without breaking. At the same time, it must also be able to resist the corrosion and wear of slurry.
[0005] In the prior art, the lining material of the SAG mill is generally made of high manganese steel or high chromium cast iron. However, due to the low basic strength and poor deformation resistance of high manganese steel, it is easy to produce plastic deformation during use, causing the fastening bolts to break, and on the other hand, it suffers from serious weight loss due to wear and has a short service life. High chromium cast iron materials have high strength and low toughness, and are prone to breakage during use, which also reduces their service life. This greatly increases the operating and production costs of the SAG mill. Therefore, in order to increase the service life of the SAG mill lining, it is particularly important to upgrade the SAG mill lining material and preparation process, and to research and develop wear-resistant linings and preparation processes suitable for SAG mills that have important academic significance and economic value. Summary of the invention
[0006] The purpose of the present invention is to provide a wear-resistant lining material and preparation method for a semi-autogenous mill, which has a reasonable strength and toughness match and a certain corrosion resistance, can be used for a long time in a slurry with a large impact load and a certain corrosive medium, and meets the requirements of the lining for the use environment.
[0007] To achieve the above object, the present invention provides a wear-resistant lining material for a semi-autogenous mill, comprising the following weight components: C: 0.70-0.76wt%, Si: 0.50-0.75wt%, Mn: 0.50-0.80wt%, P: ≤0.04wt%, S: ≤0.04wt%, Cr: 2.00-2.50wt%, Mo: 0.15-0.30wt%, V: 0.10-0.20wt%, Cu: 0.10-0.20wt%, Re: ≤0.03wt%, and the balance is Fe.
[0008] Preferably, it comprises the following components by weight: C: 0.7360wt%, Si: 0.7140wt%, Mn: 0.7350wt%, P: 0.0212wt%, S: 0.0130wt%, Cr: 2.0100wt%, Mo: 0.1870wt%, V: 0.1060wt%, Cu: 0.1500wt%, Re: ≤0.0005wt%, and the balance is Fe.
[0009] To achieve the above object, the present invention also provides a method for preparing a wear-resistant lining material for a semi-autogenous mill, comprising the following steps: S1. Add scrap steel and carburizer into a medium frequency induction furnace for smelting according to weight. After all the furnace materials are melted, add ferromolybdenum, high carbon ferrochrome, ferromanganese, ferrosilicon, ferrovanadium and copper plate in sequence for alloying to obtain a completely molten alloy. S2, deoxidizing the alloy obtained in S1 and raising the temperature to obtain molten steel, with the tapping temperature being 1600-1650°C; S3, slag-making agent and covering insulation agent are added to the molten steel in the ladle furnace, rare earth element Re is added in the ladle furnace by the wrapping method, and the molten steel is cast into the kiel sample after being calmed for 5-10 minutes to obtain a blank; S4. The blank is annealed by heating and keeping at 1000℃~1100℃ for 3.5~4.5h, heated and kept at 850℃~900℃ for 1~3h, air-cooled to below 600℃, and then air-cooled to room temperature, and finally heated and kept at 500℃~600℃ for 1~3h for stress relief and tempering to obtain the lining material sample.
[0010] Preferably, in S1, the mass ratio of the scrap steel, the carburizer, ferromolybdenum, high carbon ferrochrome, ferromanganese, ferrosilicon, ferrovanadium and copper plate is 923:2:5:50:7:9:4:2.
[0011] Preferably, in S2, the steel tapping temperature is 1620°C.
[0012] Preferably, in S3, the kiel specimen is molded using water glass sand.
[0013] Preferably, in S3, the rare earth element Re includes lanthanum and cerium.
[0014] Preferably, S4 is specifically: The blank was annealed at 1050°C for 4 hours, heated at 880°C for 2 hours, air-cooled to 600°C, and then air-cooled to room temperature. Finally, it was heated at 550°C for 2 hours for stress relief and tempering to obtain the lining material sample.
[0015] Therefore, the present invention adopts the above-mentioned wear-resistant lining material and preparation method for a semi-autogenous mill, and the beneficial effects are as follows: (1) The lining material designed in the present invention adds a certain amount of rare earth elements to high-carbon low-alloy steel, making full use of the strengthening mechanism of alloy elements. At the same time, the purification, modification and alloying effects of rare earth elements in steel improve the purity of the cast steel, change the morphology of sulfide and silicate inclusions, refine the grain size and pearlite lamellar spacing of the cast steel, and improve the strength and toughness of the cast steel. Since the rare earth elements are solid-dissolved in the cast steel, an oxide film is easily formed, thereby improving the corrosion resistance of the cast steel and increasing the service life of the lining. The lining can be used for a long time in slurries with large impact loads and certain corrosive media, meeting the requirements of the lining for the use environment.
[0016] (2) The preparation method designed by the present invention adopts medium frequency induction furnace steelmaking and water glass sand casting to make the melt uniformly mixed, remove impurities and gases, and improve the purity of the melt; heating at 1050℃ for diffusion annealing, heating at 880℃ and air cooling to 600℃, then air cooling and heating at 550℃ for stress relief tempering to eliminate the residual stress inside the material. The structure of the liner produced is ultra-fine pearlite + carbide, with an average hardness of 35.2HRC and an average impact toughness of 137.34 (J / cm 2 ), the total weight loss after 5 times of abrasive wear is 0.2703g, which meets the requirements for the use of the semi-autogenous grinding mill.
[0017] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an electron microscope image of the surface morphology at 20 μm of an embodiment of a wear-resistant lining material for a semi-autogenous mill and a preparation method of the present invention; Figure 2 This is an electron microscope image of the surface morphology at 1 μm of an embodiment of a wear-resistant lining material for a semi-autogenous mill and a preparation method of the present invention; Figure 3 This is an electron microscope image of the fracture morphology at 10 μm of an embodiment of a wear-resistant lining material for a semi-autogenous mill and a preparation method of the present invention; Figure 4 This is an electron microscope image of the surface morphology after wear at 50 μm of an embodiment of a wear-resistant lining material for a semi-autogenous mill and a preparation method of the present invention. DETAILED DESCRIPTION
[0019] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0020] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0021] Embodiment 1 A wear-resistant lining material for a semi-autogenous mill comprises the following components by weight, as shown in Table 2.
[0022] Table 2 Actual chemical composition of wear-resistant lining materials (wt%) ;
[0023] The preparation method is as follows: Use medium frequency induction furnace for smelting. First, add 923kg of scrap steel and 2kg of carburizer during the smelting process. After all the furnace materials are melted, take samples for testing. The sampling temperature is required to be greater than 1500℃. When the chemical composition meets the process requirements, add 5kg of ferromolybdenum, 50kg of high carbon ferrochrome, 7kg of ferromanganese, 9kg of ferrosilicon, 4kg of ferrovanadium, and 2kg of copper plate for alloying. After the alloy is completely melted, take samples for testing. If the chemical composition of the molten steel meets the requirements, aluminum deoxidation and temperature increase are carried out. The tapping temperature of the molten steel is 1620℃. Use the wrapping method to add 0.3kg of rare earth elements into the ladle furnace, and add slag-making agent and covering insulation agent when the molten steel is wrapped. After quenching for 7 minutes, the molten steel was cast into a Kiel specimen molded with water glass sand. After slow cooling, the Kiel specimen was sawn into a specimen blank with a size of 40×50×70 mm. It was annealed at 1050°C for 4 hours, heated at 880°C for 2 hours, air-cooled to 600°C, and then air-cooled to room temperature. Finally, it was heated at 550°C for 2 hours for stress relief and tempering to obtain a lining material specimen.
[0024] Experimental Testing The structure and mechanical properties of the liner prepared in Example 1 were tested.
[0025] (1) Metallographic structure testing: The sample preparation process is as follows: the liner is cut by a wire cutting machine to obtain a cutting sample size of 20×20×15mm. It is flattened by a belt grinder, ground with 240#, 320#, 600#, and 800# sandpaper, and then polished with flannel. The prepared metallographic sample is corroded by 4% nitric acid alcohol solution.
[0026] The metallographic structure was observed using a Zeiss AX10 metallographic microscope. Figure 1 As shown in Figure 2, the lamellar spacing of pearlite structure was measured using a TescanMira3 scanning electron microscope. Figure 2 shown.
[0027] Depend on Figure 1 It can be seen that the wear-resistant lining material is heated at 1050℃ for 4h annealing combined with heating at 880℃ for 2h and air-cooling to 600℃, and then air-cooling + tempering at 550℃. The metallographic structure is composed of pearlite + unmelted carbide. Figure 2 It can be seen that the average interlamellar spacing of pearlite is 0.137µm, which belongs to the category of ultra-fine pearlite structure. This ultra-fine pearlite structure can greatly improve the strength and toughness of the material.
[0028] (2) Hardness test: The sample preparation process is as follows: the liner is cut perpendicular to the length direction by a wire cutting machine and then ground flat by a belt grinder. The hardness value of the cross section of the sample is measured by a R(D)-150A1 material hardness testing machine, starting from 3mm from the surface to 3mm from the opposite side, and 5 points are selected for the average measurement. The test results are shown in Table 3.
[0029] Table 3 Rockwell hardness of lining plate ;
[0030] As shown in Table 3, the cross-sectional hardness of the lining material after heat treatment is relatively uniform, with a variation range of only 34.5HRC~36.5HRC and an average value of 35.2HRC. This shows that the wear-resistant lining material has a small fluctuation range of internal and external hardness after heat treatment. During use, the wear resistance is stable and there will be no local rapid wear. This value is 15.2HRC higher than the highest value of 20HRC of high manganese steel in the prior art.
[0031] (3) Impact performance test: The liner was cut into 12×12×55mm impact specimen blanks by wire cutting machine, 3 pieces per group. Then it was ground into 10×10×55mm standard non-notched impact specimens by grinder. The Charpy impact test was carried out on the specimens by N1500C material impact testing machine. The test results are shown in Table 4.
[0032] Table 4 Impact performance of liner ;
[0033] It can be seen from Table 4 that the toughness of the unnotched impact specimens is greater than 100 (J / cm 2 ), the fluctuation range is 121.31-166.04 (J / cm 2), its average impact toughness is 137.34 (J / cm 2 The value is similar to the impact toughness of high manganese steel in the prior art, 196 (J / cm 2 ) compared to the 2 ), but such impact toughness can fully meet the use requirements of large semi-autogenous mills, indicating that the lining plate prepared by this material and heat treatment process will not break during use, allowing the equipment to operate stably.
[0034] The fracture of the impact specimen was observed using a Sigma300 scanning electron microscope. The fracture morphology of the specimen was dimple + quasi-cleavage fracture. Figure 3 It is further shown that the liner has good toughness and can meet the requirements of strong impact load of large semi-autogenous mill.
[0035] (4) Abrasive wear detection: Preparation of abrasive wear specimens: 3 specimens per group, specimen size: Φ4×20mm.
[0036] The experiment was conducted on an abrasive wear tester model ML-100, with the following experimental parameters: load 2.45Kg, motor speed 60 rpm, wear disc radius 100mm, wear sandpaper 180 mesh. Each sample was worn 5 times in the experiment, and the sandpaper was replaced once each time. The total weight loss of 5 wears was calculated by the weight loss method. The experimental results are shown in Table 5.
[0037] Table 5 Experimental results of liner abrasive wear ;
[0038] It can be seen from Table 5 that the average weight loss due to wear is 0.2703 g and the weight loss rate is 14.71%, which indicates that the material has good wear resistance under the experimental conditions and is fully suitable for use under the working conditions of large semi-autogenous mills.
[0039] The surface morphology of the wear-resistant material sample after five times of abrasive wear was observed using a Tescan Mira3 scanning electron microscope. Figure 4 The worn surface morphology of the samples is block grinding formed by micro-cutting furrows + tearing pits + repeated plastic deformation, which further proves that the material has good wear resistance.
[0040] Therefore, the present invention adopts the above-mentioned wear-resistant lining material and preparation method for semi-autogenous mill, which has reasonable strength and toughness matching and certain corrosion resistance, and its average hardness value is 35.2HRC, and the average impact toughness is 137.34 (J / cm 2), the total weight loss after 5 times of abrasive wear is 0.2703g. It can be used for a long time in slurry with large impact load and certain corrosive medium, meeting the requirements of the liner for the use environment.
[0041] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A wear-resistant lining material for a semi-autogenous mill, characterized in that: It consists of the following components by weight: C: 0.70-0.76wt%, Si: 0.50-0.75wt%, Mn: 0.50-0.80wt%, P: ≤0.04wt%, S: ≤0.04wt%, Cr: 2.00-2.50wt%, Mo: 0.15-0.30wt%, V: 0.10-0.20wt%, Cu: 0.10-0.20wt%, Re: ≤0.03wt%, and the balance is Fe.
2. The wear-resistant lining material for a semi-autogenous mill according to claim 1, characterized in that: It consists of the following components by weight: C: 0.7360wt%, Si: 0.7140wt%, Mn: 0.7350wt%, P: 0.0212wt%, S: 0.0130wt%, Cr: 2.0100wt%, Mo: 0.1870wt%, V: 0.1060wt%, Cu: 0.1500wt%, Re: ≤0.0005wt%, and the balance is Fe.
3. A method for preparing a wear-resistant lining material for a semi-autogenous mill, characterized in that: The following steps are involved: S1. Add scrap steel and carburizer into a medium frequency induction furnace for smelting according to weight. After all the furnace materials are melted, add ferromolybdenum, high carbon ferrochrome, ferromanganese, ferrosilicon, ferrovanadium and copper plate in sequence for alloying to obtain a completely molten alloy. S2, deoxidizing the alloy obtained in S1 and raising the temperature to obtain molten steel, with the tapping temperature being 1600-1650°C; S3, slag-making agent and covering insulation agent are added to the molten steel in the ladle furnace, rare earth element Re is added in the ladle furnace by the wrapping method, and the molten steel is cast into the kiel sample after being calmed for 5-10 minutes to obtain a blank; S4. The blank is annealed by heating and keeping at 1000℃~1100℃ for 3.5~4.5h, heated and kept at 850℃~900℃ for 1~3h, air-cooled to below 600℃, and then air-cooled to room temperature, and finally heated and kept at 500℃~600℃ for 1~3h for stress relief and tempering to obtain the lining material sample.
4. The preparation method according to claim 3, characterized in that: In S1, the mass ratio of the scrap steel, the carburizer, ferromolybdenum, high carbon ferrochrome, ferromanganese, ferrosilicon, ferrovanadium and copper plate is 923:2:5:50:7:9:4:
2.
5. The preparation method according to claim 3, characterized in that: In S2, the steel tapping temperature is 1620°C.
6. The preparation method according to claim 3, characterized in that: In S3, the kiel specimen is molded by water glass sand.
7. The preparation method according to claim 3, characterized in that: In S3, the rare earth element Re includes lanthanum and cerium.
8. The preparation method according to claim 3, characterized in that: S4 is specifically: The blank was annealed at 1050°C for 4 hours, heated at 880°C for 2 hours, air-cooled to 600°C, and then air-cooled to room temperature. Finally, it was heated at 550°C for 2 hours for stress relief and tempering to obtain the lining material sample.
Citation Information
Patent Citations
Chromium-molybdenum steel lining board for mills and production technique thereof
CN102534389A
Novel time-saving and energy-saving integrated heat treatment process suitable for high-carbon low-alloy wear-resistant steel
CN118186188A
Cited By
High-toughness wear-resistant lining plate material suitable for rod mill and preparation method of high-toughness wear-resistant lining plate material
CN120400718A